Exploring the effects of interchange rotations on high-intensity activities of elite futsal players - Ribeiro, J. N.; Gonçalves, B.; Illa, J.; Couceiro, M.; Sampaio, J.; Travassos, B. (International Journal of Sports Science & Coaching, 2023)
The literature lacks an understanding of the physical demands of team sports with unlimited substitutions (player interchange rotations). Because of this characteristic of the game, it is necessary to analyze the physical requirements through player rotation rather than analyzing global averages. The objective of this research is to investigate the relationship between high-intensity activities (HIA; sum of accelerations, decelerations, and high-speed running actions) performed per interchange rotations and match time variables (playtime, rest time, and work-rest ratio) in elite futsal players. A retrospective observational design was used. Twelve matches from an elite male team competing in the Premier Spanish Futsal League were analyzed using a local positioning system, yielding a total sample of 17 players. The number of HIA performed per interchange rotation varies between players and allows the identification of three distinct activity profiles—lower HIA (10 HIA), medium HIA (28 HIA), and higher HIA (38 HIA). Furthermore, these profiles were found to be stable alongside the existing interchange rotations throughout the match. Playtime (F = 40.9, p < .001) and work-rest ratio (F = 15.6, p < .001) are the time variables that best differentiate match activity profiles. Players with more playing time (4.6 ± 1.0 min) and a work-rest ratio equal to or greater than 1 (1.1 ± 0.6 a.u.) have a greater ability to repeat HIA per rotation.